1987
DOI: 10.2135/cropsci1987.0011183x002700030019x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Seedling Hydrocyanic Acid Potential and Seed Weight in Sorghum‐Sudangrass Crosses1

Abstract: The hydrocyanic acid potential (HCN‐p) of sorghum [Sorghum bicolor (L.) Moench] plants is recognized as a heritable trait, but previous studies on the mode of inheritance of HCN‐p have produced inconsistent results. The objective of this study was to investigate the inheritance patterns of seedling HCN‐p and also of seed weight in reciprocal crosses of sorghum and sudangrass [formerly S. sudanense (Piper) Stapf]. Both traits were found to be inherited quantitatively. Generation means analysis indicated that ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
5
2
0
Order By: Relevance
“…These results are consistent with previous studies (2,3,8,10) in which it was concluded that the inheritance of HCN-p in sorghum was multigenic. Even more than five allelic pairs may be involved because some of the limitations in the use of chromosomal translocations for determining the number of genes conditioning a character, as described by Scott et al (14), also would apply in the present study.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with previous studies (2,3,8,10) in which it was concluded that the inheritance of HCN-p in sorghum was multigenic. Even more than five allelic pairs may be involved because some of the limitations in the use of chromosomal translocations for determining the number of genes conditioning a character, as described by Scott et al (14), also would apply in the present study.…”
Section: Resultssupporting
confidence: 93%
“…Means for both first-leaf and shoot-remainder HCN-p showed the same sort of seed-parent influence as that previously observed by Lamb et al (1987); that is, values for sorghum X sudangrass hybrids were higher than those for sudangrass X sorghum hybrids. This was true of seedlings from both small and large seeds.…”
Section: Resultssupporting
confidence: 79%
“…Also, seeds from the sudangrass X sorghum crosses were smaller and seedlings were lower in HCN-p than corresponding seeds and seedlings from sorghum X sudangrass hybrids. The mean comparisons discussed previously and the correlations within and across entries all verify the previous research of Lamb et al (1987), which indicated that when seeds are identical with respect to genotype of both endosperm and embryo, seed weight has little if any effect on seedling HCN-p. Therefore, it is reasonable to infer than the seed-parent effect on seedling HCN-p in crosses of sorghum and sudangrass was not due primarily to the seed-parent effect on seed weight.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations